Injury reporting in Connecticut newspapers. Issue 4 (December 1998) - Voight, Bonnie; Lapidus, Garry; Zavoski, Robert; Banco, Leonard
Abstract : Objectives —To describe how newspapers report injury events and how often they contain information about injury prevention measures. Methods —A commercial service provided all newspaper clippings reporting unintentional injury events between July and September 1995 from 17 daily and 55 weekly newspapers published in Connecticut, USA. Each clipping was reviewed to determine the presence or absence of 35 content variables. Results —There were 962 articles and excluding 35 editorials, 927 reported injury events and 17% pertained to persons under 21 years. Of the 60% that described motor vehicle collisions only 3% mentioned driver alcohol use, 9% seat belt use, and fewer than 1% airbag use. In the 17 motorcycle and 44 bicycle stories, 29% and 20% respectively, mentioned helmet use. In the 16 articles about house fires only 13% mentioned smoke detector use. There were no significant differences in injury reporting by circulation size. Conclusions —Newspapers are an important source of public information but are woefully deficient in providing information on injury prevention.